Pathomorphological Changes in Calves with Intrauterine Colibacteriosis - Mironova, Anna; Suleymanov, Suleiman; Ivanov, Dmitry; Obukhov, Mikhail; Gospodinova , Alexandra (KnE Life Sciences, 2021)
Cattle provide valuable food and raw materials for various types of industry, which is why the successful development of breeding of this type of farm animal plays an important role for the economy of the Russian Federation. Unfortunately, calves, due to stressful conditions and improper maintenance, feeding and exploitation of pregnant cows, are susceptible to diseases of the gastrointestinal tract. Colibacteriosis is one of the main causes of loss of productivity and mortality of young cattle. Therefore, the study of methods for the prevention, diagnosis and treatment of this disease is an urgent problem of veterinary medicine. This article examines the clinical and pathological methods of studying calves with intrauterine colibacteriosis. The results are presented in the form of photographs of pathomorphological changes in organs and tissues with a list of eleven pathological diagnoses inherent in escherichiosis, such as dehydration, exhaustion and anemia; hemorrhagic diathesis; acute serous lymphadenitis; acute serous splenitis (septic spleen); fatty degeneration and hemorrhages in the liver; acute catarrhal bronchopneumonia, mainly of the apical and cardiac lobes; hyperemia and hemorrhage under the epi- and endocardium; acute alterative myocarditis; acute catarrhal or hemorrhagic gastroenterocolitis; hemorrhagic or acute catarrhal with banded hemorrhage proctitis; and acute serous nephritis. For the study, we selected 16 calves of Holstein-Friesian and Brown Schwyz breed from the age of newborns to two weeks of age with symptoms of toxic dyspepsia. For the pathological studies, autopsiesof 10 corpses of calves from 1 to 5 days of life were performed. Keywords: intrauterine colibacteriosis, calves, pathological changes